Composite Nanoarchitectonics of Photoactivated Titania-Based Materials with Anticancer Properties - Nefeli Papadopoulou-Fermeli; Nefeli Lagopati; Natassa Pippa; Elias Sakellis; Nikos Boukos; Vassilis G. Gorgoulis; Maria Gazouli; Evangelia A. Pavlatou (MDPI AG, 2022)
The synthesis of titania-based composite materials with anticancer potential under visible-light irradiation is the aim of this study. In specific, titanium dioxide (TiO2) nanoparticles (NPs) chemically modified with silver were embedded in a stimuli-responsive microgel (a crosslinked interpenetrating network (IP) network that was synthesized by poly (N-Isopropylacrylamide) and linear chains of polyacrylic acid sodium salt, forming composite particles. The ultimate goal of this research, and for our future plans, is to develop a drug-delivery system that uses optical fibers that could efficiently photoactivate NPs, targeting cancer cells. The produced Ag-TiO2 NPs, the microgel and the composite materials were characterized through X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), micro-Raman spectroscopy, ultraviolet-visible spectroscopy (UV-Vis), dynamic light scattering (DLS) and transmission electron microscopy (TEM). Our results indicated that Ag-TiO2 NPs were successfully embedded within the thermoresponsive microgel. Either Ag-TiO2 NPs or the composite materials exhibited high photocatalytic degradation efficiency on the pollutant rhodamine B and significant anticancer potential under visible-light irradiation.